Properties of hooked steel fibers reinforced alkali activated material concrete - Meor Ahmad Tajudin, Meor Ahmad Faris; Abdullah, Mohd Mustafa Al Bakri; Ismail, Khairul Nizar; Muniandy, Ratnasamy; Mahmad Nor, Aiman; Putra Jaya, Ramadhansyah; Ahmad Zailani, Warid Wazien (EDP Sciences, 2016)
In this study, alkali activated material was produced by using Class F fly ash from Manjung power station, Lumut, Perak, Malaysia. Fly ash then was activated by alkaline activator which is consisting of sodium silicate (Na2SiO3) and sodium hydroxide (NaOH). Hooked end steel fibers were added into the alkali activated material system with percentage vary from 0 % – 5 %. Chemical compositions of fly ash were first analyzed by using x-ray fluorescence (XRF). All hardened alkali activated material samples were tested for density, workability, and compression after 28 days. Results show a slight increase of density with the addition of steel fibers. However, the workability was reduced with the addition of steel fibers content. Meanwhile, the addition of steel fibers shows the improvement of compressive strength which is about 19 % obtained at 3 % of steel fibers addition.